Hypnoteacing Sebagai Metode Alternatif Dalam Pembelajaran Materi Keagamaan: Kajian Konsep dan Teknis Pada Pembelajaran Spritual - Nurul Istiani; Athoillah Islamy (Sustainable, 2020)
Orientation in spiritual education does not always run smoothly. One of the obstacles is related to how to use the right learning method in order to teach students spiritual intelligence properly and optimally. This study aims to explain the application of the hypnoteaching method in spiritual learning. This type of research is qualitative research in the form of a literature review. The main data source of this research is Muhammad Noer's thoughts in his book entitled Hypnoteaching For Success Learning. Meanwhile, the secondary data sources used were various studies that were relevant to the object of this research discussion. The results of this study concluded that the hypnoteaching method is a learning method that combines the teaching and learning process with hypnosis. This method can be used as a method in the spiritual learning process. In its application, the hypnoteaching method emphasizes the cognitive, affective, and psychomotor aspects of students through positive suggestions. With these steps, it is hoped that a more effective and enjoyable spiritual learning process can be realized.